slope \(\displaystyle=−{6}\)

y intercept \(\displaystyle=−{3}\)

x intercept \(\displaystyle=-{\frac{{{1}}}{{{2}}}}\)

Explanation:

the slope is the number before the x, so

slope \(\displaystyle=−{6}\)

the y intercept in the number added, so

y intercept \(\displaystyle=−{3}\)

the x intercept is where the line crosses the x axis, so it's where the y value is zero. therefore, we can say that the equation equals zero, and solve for x.

\(\displaystyle{0}=−{6}{x}−{3}\)

\(\displaystyle{3}=−{6}{x}\)

\(\displaystyle-{\frac{{{1}}}{{{2}}}}={x}\)

x intercept \(\displaystyle=-{\frac{{{1}}}{{{2}}}}\)

y intercept \(\displaystyle=−{3}\)

x intercept \(\displaystyle=-{\frac{{{1}}}{{{2}}}}\)

Explanation:

the slope is the number before the x, so

slope \(\displaystyle=−{6}\)

the y intercept in the number added, so

y intercept \(\displaystyle=−{3}\)

the x intercept is where the line crosses the x axis, so it's where the y value is zero. therefore, we can say that the equation equals zero, and solve for x.

\(\displaystyle{0}=−{6}{x}−{3}\)

\(\displaystyle{3}=−{6}{x}\)

\(\displaystyle-{\frac{{{1}}}{{{2}}}}={x}\)

x intercept \(\displaystyle=-{\frac{{{1}}}{{{2}}}}\)